Pattern of Resident Movement and Mobility from The Area of Origin to The City (Case Study in Mranggen District) - Ahmada, Naufal Haidar; Basuki, Yudi (Universitas Negeri Semarang, 2020)
The border areas of villages and cities are areas that intersect and influence each other. This was the case between Mranggen District and Semarang City. The development of Mranggen is growing rapidly along with the city of Semarang. All of this has the potential to cause changes in regional characteristics both spatially and socio-economically. This phenomenon is indicated by an increase in population, socio-economic activities as a result of increased population mobility from Mranggen to Semarang and vice versa. The purpose of this study was to analyze the movement and mobility factors of the existing population in terms of age, education level, occupation, income and expenditure and distance. This study uses crosstab sampling analysis to determine the level of relationship and population mobility that occurs. The benefit of this research is to provide input to relevant stakeholders in planning this area